Growing Without a Partner: Finding Meaning in Life for Single Career Women through Lifelong Learning - Nabila Ayniyah; Qurrota A'yuni Fitriana (Character Jurnal Penelitian Psikologi, 2026)
Women who choose to live single lives while pursuing careers are viewed as unusual in society. Understanding the meaning in life for single career women will provide insight into how they interpret their lives as individuals who live independently while facing social pressure related to their life choices and professional roles. The purpose of this study is to understand the meaning of life for single career women. This research was conducted using qualitative methods through an interpretive phenomenological study approach. Five participants aged 30-35 years with more than five years of work experience were selected purposively, with the criteria of not having a partner or being unmarried. Data were collected through semi-structured in-depth interviews and analyzed using the Interpretative Phenomenological Analysis (IPA) method. The results showed that the five participants found meaning in their lives through exploring various positive things and committing to lifelong learning, namely by continuing to open themselves up to new experiences, developing skills, and organizing themselves to live a more meaningful and purposeful life. This study highlights that meaning in life for single career women does not appear suddenly, but is formed through a process of self-reflection, acceptance, and self-development. Abstrak Wanita yang memilih menjalani kehidupan melajang sekaligus mengejar karier dipandang sebagai suatu hal yang tidak lazim dalam masyarakat. Memahami makna hidup pada wanita karier lajang akan memberikan pemahaman mengenai bagaimana mereka memaknai kehidupannya sebagai individu yang menjalani kemandirian sekaligus menghadapi tekanan sosial terkait pilihan hidup dan peran profesionalnya. Tujuan dari penelitian ini adalah untuk memahami makna hidup pada wanita karier lajang. Penelitian ini dilakukan dengan metode kualitatif melalui pendekatan studi fenomenologi interpretatif. Lima partisipan berusia 30-35 tahun dengan pengalaman kerja selama lebih dari lima tahun dipilih secara purposive, dengan kriteria tidak memiliki pasangan atau belum menikah. Data dikumpulkan dengan wawancara mendalam semi terstruktur dan dianalisis menggunakan metode Interpretative Phenomenological Analysis (IPA). Hasil penelitian menunjukkan bahwa kelima partisipan menemukan makna hidupnya melalui eksplorasi berbagai hal positif dan komitmen terhadap lifelong learning, yaitu dengan terus membuka diri pada pengalaman baru, mengembangkan keterampilan, serta menata diri agar menjalani kehidupan dengan lebih bermakna dan terarah. Penelitian ini menyoroti bahwa makna hidup pada wanita karier lajang tidak muncul secara tiba-tiba, tetapi terbentuk melalui proses refleksi diri, penerimaan, dan pengembangan diri.